CEO Characteristics and Firm Performance: Evidence from Tourism and Financial Firms Listed on Botswana Stock Exchange - Mbekomize, Christian J; Chatibura, Delly M; Baliyan, Pritika S (International Journal of Business, Economics and Management, 2021)
The paper examined the effect of Chief Executive Officers’ characteristics on the performance of listed tourism and financial firms in Botswana, for the period of 2009 to 2019. The Chief Executive Officers’ gender, tenure, nationality, share ownership, and board directorship were the independent variables while Return on Assets and Return on Equity being proxies of profitability, formed the dependent variables. Firm’s size and leverage were the control variables. Quantitative research design was employed and panel data from annual reports was analysed using correlation and regression techniques. Tenure and share ownership had a significant positive association with Return on Assets while gender, nationality and directorship had a significant negative correlation. No single independent variable had a significant association with Return on Equity. Regression results revealed that nationality had a significant negative effect on Return on Assets while share ownership had significant positive impact. The results of regression also indicate that tenure had a significantly positive influence on Return on Equity. Gender and board directorship of Chief Executive Officers did not appear to have a role in influencing the performance of firms. These results have implications on where firms’ Chief Executive Officers should be sourced, how they should be remunerated and how long they should be kept on the position.